74.7k views
1 vote
(x^2-3x+1)(x^2+2x-1) PLEASE SHOW STEP BY STEP ON HOW YOU GOT THE ANSWER

User Cching
by
4.7k points

2 Answers

3 votes

Answer:

=x4−x3−6x2+5x−1

Explanation:

(x2−3x+1)(x2+2x−1)

=(x2+−3x+1)(x2+2x+−1)

=(x2)(x2)+(x2)(2x)+(x2)(−1)+(−3x)(x2)+(−3x)(2x)+(−3x)(−1)+(1)(x2)+(1)(2x)+(1)(−1)

=x4+2x3−x2−3x3−6x2+3x+x2+2x−1

=x4−x3−6x2+5x−1

User Cubert
by
4.8k points
3 votes

Answer:

first multiply

2x-3x+1+2x+2x-1

add all like terms

3x+1-1

final answer is 3x

Explanation:

User Apogentus
by
5.5k points